1957
DOI: 10.1152/ajplegacy.1957.189.2.277
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Transfer During Hypothermia and Anoxia in Dogs

Abstract: Electrolyte changes were studied during artificial respiration and hypothermia in dogs which had been equilibrated with K42, Na24 or B82. In the hypothermic animals potassium in plasma, potassium and sodium in skeletal muscle and potassium in auricle decreased, whereas bromide in the auricle increased. In normothermic animals anoxia produced an increase of bromide in the skeletal muscle and of sodium in the auricle; potassium increased in the plasma and decreased in the myocardium. Anoxia during hypothermia re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1959
1959
1973
1973

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…1 --Gollan, Eudolph, and Olsen 3 found that in dogs induction of hypothermia to a rectal temperature of approximately 23 C. resulted in a significant decrease in potassium, increase in bromide and no change in sodium content of the atrium. These authors suggested that the increased myocardial excitability during hypothermia is caused or accompanied by a loss of potassium and an inability to extrude sodium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 --Gollan, Eudolph, and Olsen 3 found that in dogs induction of hypothermia to a rectal temperature of approximately 23 C. resulted in a significant decrease in potassium, increase in bromide and no change in sodium content of the atrium. These authors suggested that the increased myocardial excitability during hypothermia is caused or accompanied by a loss of potassium and an inability to extrude sodium.…”
mentioning
confidence: 99%
“…Xormocapneic and hypercapneic dogs that did not develop fibrillation failed to exhibit these changes. On the other hand, Swan 3 found that at a rectal temperature of 30 C. the mildly acidotic dog shows a positive balance of potassium in the myocardium, as determined by coronary arteriovenous differ- Supported in part by research grant HI798 C3 from the National Heart Institute, U.S. Public Health Service, and in part by grants from the American Heart Association and the Memphis Heart Association.…”
mentioning
confidence: 99%
“…Electrolyte studies in cooled cardiac and skeletal muscles have been reported with somewhat contradictory results. 20 " 28 It is still unknown whether or not alterations in the concentration of electrolytes occur in vascular smooth muscles during hypothermia and possibly change the response of the tissue to chemical and mechanical stimuli.…”
Section: Badeermentioning
confidence: 99%
“…Some workers have observed a fall during cooling (Munday, Blane, Chin, and Machell, 1958;Gollan, Rudolph, and Olsen, 1957;Yonce, Dykers, and McGee, 1962). Others have observed a rise in the potassium level during cooling and a fall during rewarming (Dunlop and Curnow, 1962;Sarajas, 1962).…”
mentioning
confidence: 99%